Oden Southern Ocean 2009/10 - Conductivity-Temperature-Depth (CTD) Data Collected Onboard Icebreaker Oden during February through March 2010 - Anderson, John; Swedish Polar Research Secretariat (Swedish Polar Research Secretariat, 2022)
This data set contains conductivity, temperature and depth data collected during the American-Swedish expedition Oden Southern Ocean 2009/10, which was an international research cruise using the icebreaker Oden. The expedition embarked from McMurdo Station on February 8 2010 and arrived in Punta Arenas, Chile March 12 2010. Calibrated Hydrographic Data acquired with a CTD from Pine Island Bay, Antarctica acquired during the Oden expedition OSO0910 (2010)

Data include: water depth, pressure, water temperature, salinity, conductivity, and dissolved oxygen

This data set was acquired with a Sea-Bird SBE-9 CTD.

Data can be downloaded from:
http://www.marine-geo.org/tools/search/Files.php?data_set_uid=16976

More information on the cruise, links to publications etc. can be found at http://polarforskningsportalen.se/en/antarctica/expeditions/oden-southern-ocean-2009-10

Innehåller data som samlats under den amerikanska-svenska expeditionen Oden Southern Ocean 2009/10, en internationell forskningskryssning med isbrytaren Oden.

Data inkluderar: vattendjup, tryck, vattentemperatur, salthalt, ledningsförmåga och upplöst syre.

Denna dataset förvärvades med Sea-Bird SBE-9 CTD.

Data kan laddas ned från:
http://www.marine-geo.org/tools/search/Files.php?data_set_uid=16976

Mer information om kryssningen, länkar till publikationer mm finns på http://polarforskningsportalen.se/en/antarctica/expeditions/oden-southern-ocean-2009-10
Oden Southern Ocean 2009/10 - Conductivity-Temperature-Depth (CTD) Data Collected Onboard Icebreaker Oden during February through March 2010
Keywords: WATER PRESSURE; OXYGEN; CONDUCTIVITY; WATER TEMPERATURE; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Oceans; Kust och hav